Pubertal timing in boys and girls born to mothers with gestational diabetes mellitus: a systematic review. Issue 1 (January 2021) - Subramanian, Anuradhaa; Idkowiak, Jan; Toulis, Konstantinos A; Thangaratinam, Shakila; Arlt, Wiebke; Nirantharakumar, Krishnarajah
Abstract : Context: The incidence of gestational diabetes mellitus (GDM) has been on the rise, driven by maternal obesity. In parallel, pubertal tempo has increased in the general population, driven by childhood obesity. Objective: To evaluate the available evidence on pubertal timing of boys and girls born to mothers with GDM. Data sources: We searched MEDLINE, EMBASE, CINAHL Plus, Cochrane library and grey literature for observational studies up to October 2019. Study selection and extraction: Two reviewers independently selected studies, collected data and appraised the studies for risk of bias. Results were tabulated and narratively described as reported in the primary studies. Results: Seven articles (six for girls and four for boys) were included. Study quality score was mostly moderate (ranging from 4 to 10 out of 11). In girls born to mothers with GDM, estimates suggest earlier timing of pubarche, thelarche and menarche although for each of these outcomes only one study each showed a statistically significant association. In boys, there was some association between maternal GDM and earlier pubarche, but inconsistency in the direction of shift of age at onset of genital and testicular development and first ejaculation. Only a single study analysed growth patterns in children of mothers with GDM, describing a 3-month advancement in the age of attainment of peak height velocity and a slight increase in pubertal tempo. Conclusions: Pubertal timing may be influenced by the presence of maternal GDM, though current evidence is sparse and of limited quality. Prospective cohort studies should be conducted, ideally coupled with objective biochemical tests.